Pelatihan Pembuatan Presentasi Menggunakan Canva Untuk TP PKK Kelurahan Bambu Apus Jakarta Timur - Sofyanty, Devy; Fauzi, Ahmad; Anwar, Dian Mohamad (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
This community service activity aims to improve the soft skills of TP PKK members from the by providing gracphic design using the Canva application. The method used in this community service is PLA (Participatory Learning and Action), a community empowerment method that consists of a learning process about topic and then followed by real action relevant to the empowerment material. The approach used in this program is outreach, practice, and mentoring until the training participants can get to know the Canva application, how to utilize or use the application. This activity was carried out on Juni 8 2024 involving 15 TP PKK members as partners. With support from the TP PKK members, this service activity was carried out at the gebang sari RPTRA Gebang Sari hall. Activities can run well seen from the enthusiasm of partners in following the stages of training, practice, discussion and providing motivation. The results of this activity were able to improve the participants soft skill in utilizing technology, one of which was the use of the Canva application. Based on the results of the questionnaire that was distributed to 15 participants, it showed that 100 %of the 30 participating partners agreed that after followig and practicing the programs they had participated in, participants were able to create graphic design through the Canva application